Methodical Ways of Studying of the Story of I.P. Shchegolikhin «Three in the Car» In (Journal of Educational Sciences, 2018)
In the article methodical methods of studying of the story of I.P. Shchegolikhin «Three in the car» are described. Knowledge of students will be strong if to study the story «Three in the Car» in the context of I.P. Shchegolikhin’s creativity. These contexts were built in a format of the analysis of titles of literary works of I.P. Shchegolikhin. On the practical occupation devoted to studying of this work, the teacher carries out the analysis of titles of works of the writer. On practical occupation also such important artistic touch in I.P. Shchegolikhin’s creativity as a metaphor which is closely connected with poetics of his prose is considered. Besides, the metaphor is reflected even in titles of works of I.P. Shchegolikhin. The analysis of titles of works and a metaphor allowed students to realize communication of these elements of poetics of the story «Three in the Car» with its subject, the ideas and a genre. Occupation is constructed in a heuristic format so that the student has to find independently a problem, offer a way of its decision, be able to look for and prove own decision.Key words: heuristic training, interactive occupation, methodical receptions, studying, metaphor, story.